2020
DOI: 10.1155/2020/8720450
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phacoemulsification on Anterior Chamber Angle in Eyes with Medically Uncontrolled Filtered Primary Angle-Closure Glaucoma

Abstract: Purpose. To evaluate the effect of phacoemulsification and intraocular lens (IOLs) implantation in eyes with medically uncontrolled primary angle-closure glaucoma (PACG) previously treated with trabeculectomy and to quantify the anatomical changes in the anterior chamber angle by ultrasound biomicroscopy (UBM). Methods. Forty-four eyes of 37 consecutive patients with medically uncontrolled PACG coexisting cataracts with a surgical history of trabeculectomy were included in this study. Each patient underwent ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…They reported decrease IOP and improved vision in these patients. 15 Our study showed an initial increase and a later decease in IOP at one month in glaucomatous as well as non-glaucomatous eyes. However, Majstruk reported a modest decrease in IOP even at one year after surgery.…”
Section: A H E a D O F P R I N Tsupporting
confidence: 57%
“…They reported decrease IOP and improved vision in these patients. 15 Our study showed an initial increase and a later decease in IOP at one month in glaucomatous as well as non-glaucomatous eyes. However, Majstruk reported a modest decrease in IOP even at one year after surgery.…”
Section: A H E a D O F P R I N Tsupporting
confidence: 57%
“…Phacoemulsification can relieve pupillary occlusion and reduce the angle of crowding caused by the thickened, anteriorly located lens. Mechanical deepening of the anterior chamber with viscoelastic infusion and saline during phacoemulsification (Zuo et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The insufficiency of LPI for the treatment of acute primary closed angle is proven by the fact that 30% of patients subsequently require trabeculectomy due to IOP decompensation 58. In addition, late LE due to the formation of goniosynechia in the eyes that had previously undergone trabeculectomy59 or LPI in subsequent selective laser trabeculoplasty60 does not lead to a decrease in ITC. Moreover, early LE can prevent the development of a pathologic process in the trabecular meshwork as PACD progresses61 and the development of PACG 16,62.…”
Section: Discussionmentioning
confidence: 99%